The Effect of Debt-to-Equity Ratio and Current Ratio on Stock Price with Earnings per Share as an Intervening Variable in Garment and Textile Subsector Companies Listed on the Indonesia Stock Exchange for the 2020–2024 Period - Irbah Qurrotu’aeni; Erwin Budianto (Interdisciplinary Social Studies, 2026)
This study aims to analyze the effect of the Debt-to-Equity Ratio (DER) and Current Ratio (CR) on stock prices, with Earnings per Share (EPS) as an intervening variable, in garment and textile subsector companies listed on the Indonesia Stock Exchange for the 2020–2024 period. This study employs an associative quantitative approach using secondary data obtained from financial statements and stock price records. The research sample consisted of 10 companies selected through purposive sampling, yielding a total of 50 units of research data. Data analysis was conducted using path analysis in SPSS, with mediation testing performed using the Sobel test. The results indicate that the Debt-to-Equity Ratio (DER) has no significant effect on Earnings per Share (EPS), whereas the Current Ratio (CR) has a significant effect on Earnings per Share (EPS). Earnings per Share (EPS) has no significant effect on stock price. Both the Debt-to-Equity Ratio (DER) and the Current Ratio (CR) significantly affect stock price. The results of the Sobel test show that Earnings per Share (EPS) does not mediate the effect of the Debt-to-Equity Ratio (DER) on stock price but does mediate the effect of the Current Ratio (CR) on stock price. This study concludes that a company's liquidity plays an important role in the formation of stock prices, both directly and through earnings per share, whereas capital structure exerts a direct effect without the mediating role of profitability.